The role and management of Eucalyptus in Lode Hetosa district, central Ethiopia - Mekonnen, Z.; Kassa, H.; Lemenh, M.; Campbell, Bruce M. (2007)
The growing demand for construction and fuel wood and the wide adaptation of Eucalyptus to the different agro-ecological zones of the country are resulting in increased plantation of Eucalyptus by smallholders, but the policy environment in Ethiopia discourages farmers from planting this exotic. While rural and urban households supported the planting of Eucalyptus, district level politicians opposed its planting, and researchers had reservations about it. The opposition of the politicians appears to be founded on fears of damage to the ecosystem. This study was conducted to examine the contribution of Eucalyptus to meeting wood and cash needs of rural households, onfarm management of Eucalyptus, and the perception of stakeholders in Central Ethiopia about this tree. Of tree species, Eucalyptus was ranked first by farmers, indicating conflicts between policy makers and local communities over market needs for Eucalyptus wood. A market survey showed that 74% of firewood sold in the district capital was Eucalyptus. The tree generated a quarter of annual cash incomes of rural households, and contributed significantly to subsistence. Almost half of the farmers had overstocked their Eucalyptus woodlots, indicating that plantation management needs improving. The study shows that Eucalyptus plays an important role in the livelihoods of smallholders, and that attempts to discourage Eucalyptus, in the absence of viable alternatives, will worsen wood scarcity in the Ethiopian highlands.